Formal property rights in the face of the substantial right to housing. - Lo Piccolo, Francesco; Giampino, Annalisa (TU Wien, 2016)
This paper explores the dichotomy between formal property rights and use value of rights in the field of the right to housing for homeless people, focusing on the entitlement of the squatting practices to claim the collective rights in the public domain. This collective claim can be considered an alternative to the traditional conception of the public property as ´exclusive domain of State. In the cities of Southern Europe, urban space has become an object of contention by groups of inhabitants, who are organized at various levels, and an object of claiming - through illegal (although not illegitimate) forms of occupation of public or social private properties - the right to housing as primary expression of the broader right to the city . Starting from the evidences emerging from the informal practices of reappropriation of spaces (occupied spaces) in the case study of Palermo, the aim of the paper is to demonstrate that the use value is applicable in the housing field through the lens of the right to the city. The self-help housing practises suggest a "third way" in the theoretic interpretation on the right to housing, overtaking the division between natural rights and legal rights.
Keywords: Stadtsoziologie; Eigentumsrecht; Öffentlicher Raum; Stadtraum; Obdachlosigkeit; Wohnrecht; Fallstudie